2017
DOI: 10.3390/nu9020104
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Selected Serum Metallic Elements and Obesity in Children and Adolescent in the U.S.

Abstract: The prevalence of obesity has increased at an alarming rate worldwide. Metallic elements are involved in the pathogenesis of obesity and related diseases. To date, whether environmental exposure to metallic elements has effects on obesity in children and adolescents is still unclear. The aim of the current study was to investigate the association of blood metallic elements with obesity in U.S. children and adolescents. This cross-sectional study was performed with 5404 children and adolescents (6–19 years, 274… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
86
6
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 60 publications
14
86
6
5
Order By: Relevance
“…Fan et al [17] used data from the NHANES, conducted in 2011-2014, and researched the relationship between serum copper and serum lipids in children and adolescent. Fan's study found that there was a positive association between serum copper and TC level, but no statistically significant association between serum copper and LDL cholesterol and TG [17]. Another US study conducted by Neggers et al [22] reported no association between serum copper and lipid profile levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fan et al [17] used data from the NHANES, conducted in 2011-2014, and researched the relationship between serum copper and serum lipids in children and adolescent. Fan's study found that there was a positive association between serum copper and TC level, but no statistically significant association between serum copper and LDL cholesterol and TG [17]. Another US study conducted by Neggers et al [22] reported no association between serum copper and lipid profile levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental studies in animals [13][14][15] consistently found that severe copper deficiency could raise serum cholesterol, whereas, results of studies on the effect of serum copper on lipid metabolism in human subjects were inconsistent. Most studies suggested that serum copper level was positively associated with TC [16][17][18], LDL cholesterol [16,19], or TG [16,20,21]. However, some studies found no evidence of associations between serum copper and TC [20], TG [17,18,22], LDL cholesterol [17,23], and HDL cholesterol [16,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A associação positiva entre a hipercolesterolemia e as concentrações séricas e plasmáticas de zinco foi também observada por Fan et al 29 e Garcia et al 13 em crianças e adolescentes obesos nos Estados Unidos e escolares no México, respectivamente. Evidências sugerem que a concentração de zinco pode atuar de forma indireta no aumento de colesterol sérico total com a zinco-α-2 glicoproteína (ZAG), uma proteína que induz a mobilização de lipídios no tecido adiposo, com aumento das concentrações séricas de triacilgliceróis e colesterol 30 .…”
Section: Discussionunclassified
“…Pesquisas também realizadas com crianças pré-púberes obesas iranianas 31 demonstraram uma redução do colesterol sérico de forma significante naquelas que foram suplementadas com zinco. A associação entre a hipercolesterolemia e o zinco sérico pode ser diferente em populações obesas com baixa expressão da ZAG ou com alterações em outros parâmetros bioquímicos, como altas concentrações de leptina e baixas de adiponectina 29 . Mais estudos são necessários para comprovar a causalidade entre essas relações.…”
Section: Discussionunclassified